Do jornalismo na fabulação do real: narrativa jornalística e ficção - Gonring, Denise (2007)
This essay has the objective of noticing to what extent the journalist sees himself as an announcer of reality and if he believes that his duty is to faithfully reproduce the facts according to a supposed truth or to be just one more part in the process in which reality turns into news. In a world that truth is constantly called into question, which happens more intensely in the academic world, we could suppose a total disbelief in the existence of these concepts. However, we maintain the thesis that the journalist, as well as human kind as a whole, needs these concepts to follow his way and reinforce his control over a supposed reality which bases civilization